The Impact of Model Contracts on the Principle of Willpower - Raza, Assist. Prof. Dr. Afan Abdulaziz (Journal of Legal and Political Studies, 2019)
The signing of contracts in general without any examination of their terms and without inquiring about the legal consequences, especially when the lack of experience of the average person (consumer) against the other party (professional), which may include many of the conditions arbitrary and unfair preparation in the form of model contracts lead to imbalance In contractual obligations in a manner that achieves the greatest interest of the professional, even at the expense of the other party is inexperienced, so problems of contractual imbalance require seeking solutions available to the weak party inexperienced, as traditional legal principles and general provisions We have found it necessary to look for special rules that protect the weak party in the contractual relationship by tracing the legislator's role and indicating the success of the legislative solutions, in addition to the extent of the judiciary's intervention in interpreting the contractual provisions and the impact on the rebalancing To contractual obligations.
Keywords: unfair preparation; contractual imbalance; examination; traditional legal principles